Structures for hunting and grazing: A pre-Hispanic legacy - Aguilar Meza, Trinidad (2018)
The article presents findings of archaeological explorations without excavation, carried out in the high Andean communities of Waqoto, La Raya and Qelloqocha, in the department of Cusco. The objective was to identify evidence of hunting and camelid grazing, for the recognition of the associated structures, their characteristics and their functionality, in correlation with the ethnographic data and the information left by the chroniclers of the Spanish Conquest. The kanchas, used for the grazing of llamas and alpacas, associated with the houses, these are basic modules to develop the annual grazing cycle, while the traps are used for the capture of vicuñas (Aguilar, 1995). The sites where the structures were identified are above 3,900 m. n. m. In Waqoto the economic activity is mixed: agriculture, grazing, and the extraction and quarrying of andesite rock are practiced on the same altitudinal floor. The Raya is known for its ability to graze, but you can also grow high-altitude products such as bitter potato, quinoa, qañihua, year and goose. In Quelloqocha, only camelids are grazed, while in the lower parts, at the level of the Langui-Layo lagoon, agriculture is practiced.